Designing Information System Evaluation Of Lecturer Teaching Activities As An Implementation Of Internal Quality Guarantee System In The Unas Information System Study Program: Designing Information System Evaluation Of Lecturer Teaching Activities As An Implementation Of Internal Quality Guarantee System In The Unas Information System Study Program - M Alwi Saepul Zaman; Septi Andryana; Ratih Titi Komalasari (Institute of Computer Science (IOCS), 2020)
As technology advances fast and offers many conveniences. for humanity to complete good work in the fields of life, business and education. Quality Assurance Unit Unit Penjaminan Mutu (UPM) of Nationa University (UNAS) Information System Programas part of the Quality Assurance Agency Badan Penjaminan Mutu (BPM). UNAS to guarantee the safety activities of lecturers in the UNAS information system study program, in order to guarantee the quality of education. The implementation of an ongoing monitoring process requires a computerized system, with the hope to improve the quality and strengths in the evaluation process of improving lecturer competence. The evaluation process is still manual. The use of this manual system has not been maximized, and this concerns evaluation results that are prone to human error, such as incorrect data entry, the evaluation process and results are relatively longer. Storing information needed to improve lecturers' quality assurance is always late. therefore, an information system is needed that is expected to help the quality assurance unit (UPM). UNAS information system study program. In the data processing supported by the lecturer. The author wants to discuss web-based systems using the PHP framework namely Code Igniter (CI v.3) and MySQL DBMS. By using the method of SDLC design waterfall (waterfall) and system testing using the black-box method.